2001
DOI: 10.3168/jds.s0022-0302(01)74577-8
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production of Fall-Calving Dairy Cows During Summer Grazing of Grass or Grass-Clover Pasture

Abstract: Milk production of fall-calving dairy cows during subsequent summer grazing was evaluated in two consecutive years using a total of 80 mid- to late-lactation Holsteins. Cows calved during September and October and grazed from April to August in the following year. In yr 1, 27 cows grazed a native grass pasture and 13 cows grazed a native grass-clover mixed pasture containing 26% red clover and white clover. In yr 2, 40 cows grazed native grass pasture as one group. Also, cows in yr 2 were administered bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…While ingested pasture of Period 2 had high dietary NDF and low digestibility compared to pasture in Period 1, DMI of cow was not different between periods. This suggested that physical fill of the rumen may not have been a limiting factor for pasture intake, in agreement with Wu et al (2001). Eating time and bouts was significantly higher in treatment G than C (Table 2), in which may be reflected that the size of manger was not enough to offer to cows the sufficient amount of pasture during each eating bouts.…”
Section: Pasture Intake and Chewing Behaviorsupporting
confidence: 76%
“…While ingested pasture of Period 2 had high dietary NDF and low digestibility compared to pasture in Period 1, DMI of cow was not different between periods. This suggested that physical fill of the rumen may not have been a limiting factor for pasture intake, in agreement with Wu et al (2001). Eating time and bouts was significantly higher in treatment G than C (Table 2), in which may be reflected that the size of manger was not enough to offer to cows the sufficient amount of pasture during each eating bouts.…”
Section: Pasture Intake and Chewing Behaviorsupporting
confidence: 76%
“…These estimates suggest that the intake from the pasture was not sufficient to support a higher milk yield above the energy maintenance requirement that usually substantially increases because of grazing activities (NRC, 2001). Milk decreases are a common observation when cows are changed from a total mixed ration to grazing, often accompanied with BW losses, and the change is considered to result from insufficient intake from pasture because of small bite sizes (Wu et al, 2001). Mean ruminal pH, obtained from measurements taken during a 10-h period after feeding, was low for both treatments (5.84 and 5.94 for grazing and total mixed ration, respectively, P < 0.10; Table 3), reflecting the high starch content of the diets.…”
Section: Resultsmentioning
confidence: 99%
“…Grazed cows were also offered a supplement mix at 10 kg/day (dry matter basis) using ingredients similar to those included in the concentrate portion of the total mixed ration for the other group of cows. The allowance was used to provide 40% of the total feed intake, assuming that animals would obtain 60% of their intake from the pasture based on previous season estimates (Wu et al, 2001). The use of these values before the commencement of the experiment was necessary, but as reported below, the actual amount of the supplement consumed was less than offered.…”
Section: Animals and Dietary Treatmentsmentioning
confidence: 99%
“…Interseeding legumes into perennial grass pastures often increases animal growth and milk production above that of animals grazing pure grass stands [4,5]. Most of the research on interseeding legumes into grass pastures has been conducted in the Northeastern and Midwestern USA where conditions are favorable for legume production.…”
Section: Introductionmentioning
confidence: 99%